Use of Crude Palm Oil in Warm Mix Asphalt to Mitigate Temperature Effects - Garcia Mendoza, Alan; Alzamora de los Godos Urcia, Luis Alex; Calderón Saldaña, Jully Pahola; Valladolid Marcos, Fiorella Sthefany; Pineda Medina, Javier Alejandro; Godoy Caso, Juan; Arévalo Marcos, Rodolfo (LACCEI, 2025)
This study aimed to determine the optimal percentage of crude palm oil in asphalt mixtures during production to mitigate temperature effects, using the Marshall test conducted in 2021. The research employed a deductive, quantitative approach with a retrolective and longitudinal data collection process within an experimental design framework. The findings indicate that conventional asphalt exhibits the highest specific gravity, but as the proportion of crude palm oil increases, specific gravity also rises. Regarding air voids, the null hypothesis was accepted, signifying that palm oil incorporation did not cause statistically significant variations in void content. A similar trend was observed in flow measurements, where no substantial differences were detected across experimental groups. Furthermore, the study revealed that the most significant number of air voids occurred at 1% and 1.5% palm oil concentrations, although these values did not differ markedly from other tested formulations. The highest flow values corresponded to conventional asphalt, but an increase in palm oil concentration led to a proportional rise in flow. However, the corrected stability of the asphalt mixture decreased as the palm oil content increased, with conventional asphalt demonstrating the highest stability. Additionally, the stiffness index followed a declining trend as palm oil concentration rose, indicating a reduction in the mixture’s structural rigidity.